If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6n + 1) = 62 Reorder the terms: 2(1 + 6n) = 62 (1 * 2 + 6n * 2) = 62 (2 + 12n) = 62 Solving 2 + 12n = 62 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 12n = 62 + -2 Combine like terms: 2 + -2 = 0 0 + 12n = 62 + -2 12n = 62 + -2 Combine like terms: 62 + -2 = 60 12n = 60 Divide each side by '12'. n = 5 Simplifying n = 5
| -8+3x-4=5x+10 | | 12x+4=11x+11 | | 6(3-z)*5=-z | | 9=4p+6-p | | 3x+3=8x+13 | | 200x-1400= | | 4(-3+1)=-8 | | 6q=30q | | y^5-2y^3+y=0 | | 6(3-2x)=42 | | 4(7r+3)=236 | | x+7+x+7-17=17 | | x+7+x+7-17=11 | | 3ln(2x-5)=6 | | 4x^2+8=72 | | 3ln(2x+5)=6 | | 8x-2=6x+12 | | 6x+6+2x=24 | | 36-(-4)= | | 7+x+7-17=11 | | 27=7+9+C | | -19+-2= | | 11x+12-3x=30 | | 27=7 | | bx+d=a | | 7x-2=90 | | q^2+2q-16=0 | | 5x-4=4-d | | -42+-12= | | 35=7+12+C | | 4+17x=56 | | 6x+10=90 |